Certain other countries: homicide, gender, and national identity in late nineteenth-century England, Ireland, Scotland, and Wales - Conley, Carolyn A. (History of crime and criminal justice, 2007)
Introduction -- Homicides: procedures, perceptions, and statistics -- National identity: foreigners and strangers -- Class, gender, and the fair fight -- Family and courtship -- Husbands and wives -- Children -- Conclusion -- Notes -- Bibliography -- Index